Digital infrastructure for the learning health system : the foundation for continuous improvement in health and health care : workshop series summary - Institute of Medicine (U.S.). Roundtable on Value & Science-Driven Health Care.; Grossmann, Claudia, Ph. D.; Powers, Brian, B.A.; McGinnis, J. Michael; Institute of Medicine (U.S.) (Washington, D.C. : National Academies Press, 2011)
"Like many other industries, health care is increasingly turning to digital information and the use of electronic resources. The Institute of Medicine's Roundtable on Value & Science-Driven Health Care hosted three workshops to explore current efforts and opportunities to accelerate progress in improving health and health care with information technology systems."--Publisher's description.
Includes bibliographical references.
Keywords: Medicine -- Information technology -- United States -- Congresses; Medical informatics -- United States -- Congresses; Information storage and retrieval systems -- Community health services -- Congresses; Medical policy -- United States -- Congresses; Health -- Government policy -- United States -- Congresses; Medical care -- United States -- Safety measures -- Congresses; Delivery of Health Care -- organization and administration -- United States -- Congresses; Medical Informatics -- United States -- Congresses; Health Policy -- United States -- Congresses; Learning -- United States -- Congresses; Quality Improvement -- United States -- Congresses